Antibacterial activity of plant species used for oral health against Porphyromonas gingivalis - Carrol, Danielle H.; Chassagne, François; Dettweiler, Micah; Quave, Cassandra L. (PLOS ONE, 2020)
Porphyromonas gingivalis is the keystone pathogen of periodontitis, a chronic inflammatory disease which causes tooth loss and deterioration of gingiva. Medicinal plants have been traditionally used for oral hygiene and health and might play a role as antibacterial agents against oral pathogens. In this work, we aimed to evaluate the antibacterial activity of plants used for oral hygiene or symptoms of periodontitis against P. gingivalis. We first reviewed the literature to identify plant species used for oral hygiene or symptoms of periodontitis. Then, we cross-checked this species list with our in-house library of plant extracts to select extracts for testing. Antibacterial activity tests were then performed for each plant extract against P. gingivalis, and their cytotoxicity was assessed on HaCaT cells. The selectivity index (SI) was then calculated. A total of 416 plant species belonging to 110 families and 305 genera were documented through our literature search, and 158 plant species were noted as being used by North American Native peoples Once cross-checked with the extracts contained in our library of natural products, 30 matches were identified and 21 were defined as high priority. Of the 109 extracts from 21 plant species selected and tested, 21 extracts from 11 plants had higher than 90% inhibition on P. gingivalis at 64 μg/mL and were further selected for MIC (Minimum Inhibitory Concentration) assays. Out of 21 plant extracts, 13 extracts (7 plant species) had a SI > 10. Pistacia lentiscus fruits showed the best MIC with value of 8 μg/mL, followed by Zanthoxylum armatum fruits/seeds with a MIC of 16 μg/mL. P. lentiscus fruits also showed the highest SI of 256. Most of the extracts tested present promising antibacterial activity and low cytotoxicity. Further testing for biofilm eradication and examination of activity against other dental pathogens and oral commensals should be performed to confirm the potential of these extracts as antibacterial agents. Future work will focus on application of a bioassay-guided fractionation approach to isolating and identifying the most active natural products in the top performing extracts. This study can serve as a basis for their future development as ingredients for oral hygiene products.